2020
DOI: 10.1002/adom.202000220
|View full text |Cite
|
Sign up to set email alerts
|

Quaternary Supramolecular Nanoparticles as a Photoerasable Luminescent Ink and Photocontrolled Cell‐Imaging Agent

Abstract: Photoswitchable luminescent supramolecular assemblies based on cyclodextrins have attracted considerable attention owing to their potential applications as smart materials, but most of the assemblies reported to date emit green or blue light with low contrast and high interference. In this study, novel photoluminescent red‐luminescent quaternary supramolecular nanoparticles (2) are constructed from a dithienylethene derivative (1), a β‐cyclodextrin‐functionalized ruthenium complex (Ru‐HOP‐CD), Pluronic F‐127, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“…S2 in the Supplemental Materials). 55 These supramolecular nanoparticles were watersoluble and exhibited the same photoswitching behavior as the above system. Therefore, information coding and anticounterfeiting applications were realized using the aqueous solution of supramolecular nanoparticles as ink.…”
Section: Photoresponsive Small Molecule-based Self-assemblymentioning
confidence: 82%
See 2 more Smart Citations
“…S2 in the Supplemental Materials). 55 These supramolecular nanoparticles were watersoluble and exhibited the same photoswitching behavior as the above system. Therefore, information coding and anticounterfeiting applications were realized using the aqueous solution of supramolecular nanoparticles as ink.…”
Section: Photoresponsive Small Molecule-based Self-assemblymentioning
confidence: 82%
“…The remarkable properties allow their successful application in information storage, including rapid light response, good reversibility, outstanding fatigue resistance, excellent thermal stability, and high photoisomerization quantum yield. [50][51][52][53][54][55] SP also undergoes reversible ring opening-closure photoisomerization. It becomes the purple merocyanine (MC) form under UV light irradiation, while it reverts into the colorless SP form by heating or irradiating with visible light [ Fig.…”
Section: Photoswitching Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Liu et al also attached an adamantane group to a DAE core combined with a β-CD-functionalized ruthenium complex, Pluronic F-127, and cetrimonium bromide to construct quaternary supramolecular nanoparticles. [99] Hydrophobic interactions and noncovalent host-guest interactions were key factors in the assembly process. TEM and a DLS analysis showed that the average diameter of the obtained discrete spherical nanoparticles was 175 nm, and switching the DAE units between their open and closed forms did not significantly affect their microscopic morphology.…”
Section: Host-guest Complexes Based On Daementioning
confidence: 99%
“…[207] The bioimaging potential of stimulus-responsive supramolecular assemblies has also received attention in recent years, [208] and it requires biocompatible assemblies. [209] Based on their previous research, [210] Liu et al [99] reported quaternary supramolecular nanoparticles based on a β-CD modified ruthenium complex (Ru-HOP-CD), DAE derivatives, Pluronic F-127, and cetrimonium bromide. Ru-HOP-CD emitted red fluorescence under excitation at 450 nm.…”
Section: Bioimagingmentioning
confidence: 99%